A TREATMENT OF A MULTISTEP COLLOCATION METHOD FOR THE DIRECT SOLUTION OF SECOND-ORDER ORDINARY DIFFERENTIAL EQUATIONS - Atsi, Kaze; Tumba, Pius; Suleiman, Enoch (FUDMA JOURNAL OF SCIENCES, 2024)
A research has been conducted at the Department of Mathematics, Faculty of Science, Federal University, Gashua, Yobe State to study the treatment of multistep collocation method for the direct solution of second order ordinary differential equations using a class of modified Backward Differentiation Formular (BDF)-type with one super-future point. The research has proposed the construction of a new method of solving second-order initial valued problem of ordinary differential equation. A step-number, , a number of discrete members are obtained and used in block through multi-step collocation approach. The stability properties of the newly constructed methods are investigated using written computer codes and its convergence are established. The numerical efficiency of the method has been tested on some treated second-order initial valued problems, in order to ascertain its suitability. The solutions of the problems are compared with the corresponding exact solutions and the associated absolute errors are presented. Tables and graph have been adopted in the presentation of results, and they have shown the efficiency of the new method for solving solution of second order ordinary differential equations.